دور الرقمنة في تحصين الخدمة العمومية - بن قسمية شتاتحة; د/ عبدالقادر قدوري (جامعة عمار ثليجي الاغواط, 2024)
الملخص: تتناول الدراسة موضوع دور الرقمنة في تحسين جودة الخدمات العمومية ببلدية العسافية، ولمعالجة الإشكال المطروح تم اعتماد أربع محاور شملت البيانات الشخصية للمبحوث، ثم الرقمة ثم الخدمة العمومية و العلاقة بينهما، وقد اعتمدت الدراسة على المنهج الوصفي، ووظفت الإستمارة في جمع البيانات، وفي الأخير خلصت الدراسة لإبراز الدور الهام للرقمنة في ترقية الخدمة العمومية ببلدية العسافية، وكل هذا يبين الدور المهم الذي تلعبه الرقمنة في تحسين ظروف الخدمات المقدمة للمواطنين. الكلمات المفتاحية: الرقمنة، الخدمة العمومية، تحسين، العسافية. Abstract: "A study is presented on the topic of the role of digital in improving the quality of services in the municipality of Asafiya, and it did not address the problems raised. Four axes were relied upon to show personal data for the research, then digital, then service, and competed differently. The study began on a descriptive application, and the form was used to collect data, and in the end the study concluded by highlighting the important role of digitization in the promotion service in the municipality of Asafiya, and all of this shows the important role that digitization plays in facilitating the provision of services at the forefront. Keywords: digitization, public service, improvement, Al-Asafiya.
دراسة على موظفي بلدية العسافية